Diastolic relaxation and compliance reserve during dynamic exercise in heart failure with preserved ejection fraction - Borlaug, Barry A; Jaber, Wissam A; Ommen, Steve R; Lam, Carolyn S P; Redfield, Margaret M; Nishimura, Rick A (Heart (British Cardiac Society), 2011)
BackgroundRecent studies have examined haemodynamic changes with stressors such as isometric handgrip and rapid atrial pacing in heart failure with preserved ejection fraction (HFpEF), but little is known regarding left ventricular (LV) pressure–volume responses during dynamic exercise.ObjectiveTo assess LV haemodynamic responses to dynamic exercise in patients with HFpEF.MethodsTwenty subjects with normal ejection fraction (EF) and exertional dyspnoea underwent invasive haemodynamic assessment during dynamic exercise to evaluate suspected HFpEF.ResultsLV end-diastolic pressure was elevated at rest (>15 mm Hg, n=18) and with exercise (≥20 mm Hg, n=20) in all subjects, consistent with HFpEF. Heart rate (HR), blood pressure, arterial elastance and cardiac output increased with exercise (all p<0.001). Minimal and mean LV diastolic pressures increased by 43–56% with exercise (both p<0.0001), despite a trend towards a reduction in LV end-diastolic volume (p=0.08). Diastolic filling time was abbreviated with increases in HR and the proportion of diastole that elapsed prior to estimated complete relaxation increased (p<0.0001), suggesting inadequate relaxation reserve relative to the shortening of diastole. LV diastolic chamber elastance acutely increased 50% during exercise (p=0.0003). Exercise increases in LV filling pressures correlated with changes in diastolic relaxation rates, chamber stiffness and arterial afterload but were not related to alterations in preload volume, HR or cardiac output.ConclusionIn patients with newly diagnosed HFpEF, LV filling pressures increase during dynamic exercise in association with inadequate enhancement of relaxation and acute increases in LV chamber stiffness. Therapies that enhance diastolic reserve function may improve symptoms of exertional intolerance in patients with hypertensive heart disease and early HFpEF.